The Gamification Octalysis Framework within the Primary English Teaching Process: the Quest for a Transformative Classroom (Revista Lusófona de Educação, 2018)
The “Kwesukasukela” project, which focuses on African oral tradition storytelling intermingled with the Ubuntu philosophy (Varty, 2013), has as its main aim to stimulate collaboration, communication, critical thinking and creativity, within primary school settings. In fact, through an experiential communicative approach (Fernández-Corbacho, 2014), South African storytelling can become a gamified experience and integrated into English classroom practices as a means of transformation and stimulation of social cohesion and sustainable development (Battiste, 2005).The aim of this study is to reflect upon Chou’s (2016) Octalysis framework and how it can effectively be applied in Primary English Teaching contexts. The implementation of gamification designs and practices within this type of framework allowed us to understand how we can implement effective approaches towards a transformative classroom. An ethnographic methodological approach, with triangulation of data collection tools (questionnaires, self-assessment worksheets and project work), was resorted. Gamified practices, which deal with South African cultural and linguistic varieties (Nomlomo & Zilungile, 2016) and 21st Century Learning skills, were analized (Cruz & Orange, 2016).The project’s main results show that the gamification approach can foster the development of transformative skills.Keywords: octalysis framework; english for young learners; storytelling; 21st century skills.